Burundi : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper describes economic developments in Burundi during 1993-97. The external current account (excluding grants) narrowed significantly during 1993-95, owing mainly to strong international export prices for coffee and subdued demand for imports. This trend continued in 1996 with a further compression of imports stemming from a sharp reduction in project aid and the economic embargo. The overall balance of payments shifted from a surplus of 0.2 percent of GDP in 1995 to a deficit of 7.3 percent mainly as a result of a sharp drop in external financial assistance.